Uncertainties in GPS-based operational orbit determination: A case study of the Sentinel-1 and Sentinel-2 satellites. (13th February 2020) - Kuchynka, P.; Martin Serrano, M.A.; Merz, K.; Siminski, J.
ABSTRACT: The European Space Operations Centre currently operates five Copernicus Sentinel satellites in the framework of Europe's Copernicus Earth observation programme. The routine operations rely on a daily orbit determination, carried out on-ground, consisting in a least-squares fit of a dynamical model to GPS navigation solutions generated on-board. The purpose of this paper is the estimation of realistic uncertainties on this daily determined state vector. By comparison with the orbit derived by Precise Orbit Determination, we estimate the 1-sigma errors at approximately 0.5m and 0.5mm/s. Non-stationary errors in the navigation solution preclude their characterisation with a constant covariance matrix. Error whitening is achieved by decreasing the signal-to-noise ratio in the errors through the use of underestimated weights on the data. The approach keeps the errors on the derived state vector unchanged and allows the covariance on the state vector to become realistic.